PENGARUH ETIKA PROFESI, MORALITAS INDIVIDU DAN PEMAHAMAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA AUDITOR DENGAN INDEPENDENSI SEBAGAI PEMODERASI - Sulistyowati, Lia; Panjaitan, Ingrid (Media Akuntansi Perpajakan, 2018)
The purpose of this study was to examine the effect of professional ethics, individual morality and understanding of accounting information systems on auditor performance with independence as moderation. This research was conducted at Publik Accounting Firm in DKI Jakarta. Dependent variable in this study are auditor performance. The independent variables are professional ethics, individual morality and understanding of accounting information systems. Moderation variables use independence. The population in this study Publik Accounting Firm in DKI Jakarta. Sampling technique using Purposive Sampling Method. This method requires taking as many samples as the amount determined by the researcher as a target that must be met. The sample in this study were 16 Public Accounting Firms in DKI Jakarta with 140 auditors. Methods of data collection using questionnaire method. Data testing in this study uses validity, reliability and hypothesis testing. Data processing was done using Partial Least Square (PLS) version 3.00. The statistical method used is the Path Coefficients.           The results of this study indicate that professional ethics have a significant effect on auditor performance, individual morality has a significant effect on auditor performance, understanding of accounting information systems has a significant effect on auditor performance, independence has not  significant effect on auditor performance, independence can moderate the influence of professional ethics on auditor performance, independence can moderate the influence of individual morality on auditor performance and independence can moderate the effect of understanding the accounting information system on auditor performance.Keywords: Professional Ethics, Individual Morality, Understanding of Accounting Information Systems, Auditor Performance and Independence.